Zabawa narracyjna jako strategia sprzyjająca autentycznemu uczeniu się dzieci - Joanna Szymczak (Problemy Wczesnej Edukacji)
A narrative play is a strategy which was used while creating educational situations for children aged 6 to 9, in the Narrative Environments for Play and Learning research project. The process of build-ing the strategy and implementing it in practice was monitored in order to answer the question of the strategy’s meaning for creating a teaching environment. The observation of children and teachers, the interviews with teachers and the analysis of the collected empirical material in the form of audio and video recordings lead to a conclusion that a narrative play supports developing self-regulation in students (see: Arends 1994: 488–499; Filipiak 2012: 70–79). Some specific properties and the role of a teacher who is a facilitator genuinely engaged in its construction are characteristic qualities of a narrative play. It supports developing reflectiveness and reflection regarding such aspects as: educational problems, motives of one’s behavior, one’s own beliefs.